Association Study of KCNH7 Polymorphisms and Individual Responses to Risperidone Treatment in Schizophrenia - Wang, Xueping; Su, Yi; Yan, Hao; Huang, Zhuo; Huang, Yu; Yue, Weihua (Frontiers in Psychiatry, 2019)
Risperidone has been used to treat the symptoms of schizophrenia and reduce its relapse. However, the responses to treatment show great variability among patients. The potassium channel has been reported as an effective target for antipsychotics. KCNH7, a member of the voltage-gated K+ channel Kv11 family, is primarily expressed in the brain. Here, we assessed the genetic association of KCNH7 with risperidone responses in 393 schizophrenia patients. The patients were treated with risperidone for six weeks. The reduction rates of Positive and Negative Syndrome Scale (PANSS) scores were determined to quantify drug response. We also examined the associations between six single-nucleotide polymorphisms (SNPs) of KCNH7 and the risperidone responses for a total of six weeks. The SNP rs77699177 (C>T) in the KCNH7 gene intron was significantly associated with the treatment response reflected by the PANSS reduction rate (CC, 55.8 ± 23.0; TC, 70.9 ± 20.3, P = 0.000110), indicating that patients with the TC genotype have better efficacy for antipsychotic therapy. The rs2241240 SNP also showed a significant association with treatment responses after 6 weeks of treatment (P = 0.00256). The findings indicate that the voltage-gated K+ channel KCNH7 is a potential functional marker for the identification of the response to risperidone treatment in schizophrenia patients.